Quality Of Algebra Questions to Measure Mathematical Literacy Ability Using Partial Credit Model - Wahdana, Akfi Hikmah; Pambudi, Didik Sugeng; Kurniati, Dian; Kristiana, Arika Indah; Alfarisi, Ridho (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
Mathematical literacy skills require someone to understand, analyze, interpret, evaluate and synthesize knowledge obtained from the problems faced by modeling them into appropriate solutions in solving a problem effectively. The need to develop questions according to students' daily problems can familiarize students with mathematical literacy. The research developed mathematical literacy test questions on the theme of tobacco farming in the Puger Jember area to measure students' mathematical literacy abilities at the high school level. The research method used is Research and Development (R&D) using the Thiagarajan model which is modified into three stages, namely definition, planning and development. Field trial results were analyzed using Ministep software with Rasch modeling using the Partial Credit Model (PCM) method. The results obtained from the ten questions that were developed can be said to be fit, with the reliability of 139 interactions between students and the question items, the quality is still poor, 75 students' interactions between students and the question items are of good quality. The item reliability of the literacy questions developed was 0.80 in the first 75 samples, 0.95 in the next 75 samples and 0.89 in the last 64 samples, indicating that the questions developed were good and able to measure students' abilities well.